State Secrets in the Perspective of Public Transparency (Study of the journalism code of ethics) - Hermanto, Budi (UIR Press, 2020)
Good governance is a government that is transparent, open, and participatory. Includes the whole process of managing public resources since the process of decision making, implementation, and evaluation. The benefits of freedom of information are not only to create a government that is clean, efficient and able to prevent corruption, but also to improve the quality of public participation in the process of making public policies, and supervising their implementation. The main problem raised in this study is how to state secrets from the perspective of public transparency. study of Undang-Undang No. 40 the year 1999 concerning the press and the journalistic Code of Ethics and the obstacles in trying to obtain information.